2007
DOI: 10.1111/j.1365-2648.2007.04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between burnout and occupational stress among nurses in China

Abstract: It is important to reduce occupational stress in nurses and to strengthen their coping resources to prevent burnout. This could be achieved with job redesign, modification of shiftwork systems, and by offering occupational health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 11 publications
(14 reference statements)
11
144
2
9
Order By: Relevance
“…Dimensions of stress become more strongly correlated with Emotional exhaustion across time whereby three dimensions become correlated with Depersonalisation and this is in line with the study of Wu et al (2007); however, the present study has the advantage of repeated measures. Higher Emotion-oriented coping at wave 1 is correlated with higher dimension of stress and negative aspects of burnout and the negative effect of Emotionoriented coping is demonstrated by it predictive ability for all aspects of stress and the 22 negative dimensions of burnout.…”
Section: Coping Strategies Stress and Burnoutsupporting
confidence: 88%
See 1 more Smart Citation
“…Dimensions of stress become more strongly correlated with Emotional exhaustion across time whereby three dimensions become correlated with Depersonalisation and this is in line with the study of Wu et al (2007); however, the present study has the advantage of repeated measures. Higher Emotion-oriented coping at wave 1 is correlated with higher dimension of stress and negative aspects of burnout and the negative effect of Emotionoriented coping is demonstrated by it predictive ability for all aspects of stress and the 22 negative dimensions of burnout.…”
Section: Coping Strategies Stress and Burnoutsupporting
confidence: 88%
“…Despite stress leading nurses to seek social support (LeSergent & Hanley 2005), a recent study by Wu et al (2007) demonstrated that burnout amongst nursing staff was related, amongst other things, to increased level of occupational stress. Although stress is normal in a range of circumstances (Smith & Fawcett 2006) the negative consequences arising from workload factors associated with stress, such as increasing patient load, can lead to emotional exhaustion, or burnout (Maslach & Jackson 1986), a concept that will be described below.…”
Section: Outcomes Of Stressmentioning
confidence: 99%
“…A typically-related topic is the one of job satisfaction which is extremely important for the productiveness and performance in every occupational sector (Spector, 1997, Brown et al, 1993, Judge et al, 2001). Furthermore, higher levels of job satisfaction can ensure lower absenteeism (Wu et al, 2007), and satisfied employees are more likely to be satisfied with their lives (Lease, 1998). There is also a strong link between job satisfaction and organizational commitment (Alpader, 1990).…”
Section: Introduction and Aims Of The Studymentioning
confidence: 99%
“…According to two European epidemiological studies, burnout affects approximately 25% of all the nurses [6]. Working under pressure, stress and dissatisfaction with the working hours, a high workload, lack of autonomy, conflicts with physicians and non supportive work conditions are some of the negative factors which are seen among nurses [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%